On the apparent labio-velar nasals of Kam - Solnit, David B. (2024)
In historical linguistics, certain commonplace sound changes can be presumed to happen in only one direction, usually for readily apparent phonetic reasons. Palatalization of consonants is an obvious example: it is easy to understand why a front vowel or semivowel should pull a non-palatal consonant towards a palatal point of articulation, but it is hard to imagine why a palatal consonant would ever factor itself out into, e.g. a velar stop plus a palatal semivowel. Again, a medial liquid often turns into a medial palatal semivowel, but we would be skeptical of a proposed sound change *p j - > p 1- . Vowels seems to be less subject to this sort of directionality, but nasalization might be an instance: we expect that nasalized vowels will arise from the influence of neighboring nasal consonants, and not the other way around.